Early and Late-Term Follow-Up Results of Patients Diagnosed with Aortic Aneurysm or Aortic Dissection with Aortic Regurgitation Undergoing Aortic Valve Repair or Valve-Sparing Aortic Surgery - Yiğit,Görkem (2021)
Abstract Introduction: Valve-reimplantation and remodelling techniques used in aortic reconstruction provide successful early, mid, and long-term results. We present our early and late-term experience with 110 patients with aortic regurgitation (AR) who underwent aortic valve repair (AVr) or valve-sparing aortic root surgeries (VSARS) due to aortic dissection or aortic aneurysm. Methods: Nine hundred eighty-two patients who underwent aneurysm or dissection surgery and aortic valve surgery between April 1997 and January 2017 were analysed using the patient database. A total of 110 patients with AR who underwent AVr or VSARS due to aortic dissection or aortic aneurysm were included in the study. Results: In the postoperative period, a decrease was observed in AR compared to the preoperative period (P<0.001); there was an increase in postoperative ejection fraction (EF) compared to the preoperative values (P<0.005) and a significant decrease in postoperative left ventricle diameters compared to the preoperative values (P<0.001). Kaplan-Meier analysis revealed one, two, four, and five-year freedom from moderate-severe AR as 95%, 91%, 87%, and 70%, respectively. Freedom from reoperation in one, two, and five years were 97.9%, 93.6%, and 81%, respectively. Eight patients (7.4%) underwent AVr during follow-up. Out of the remaining 100 patients, 13 (12%) had minimum AR, 52 (48%) had 1st-2nd degree AR, and 35 (32%) had 2nd-3rd degree AR during follow-up. Conclusion: For the purpose of maintaining the native valve tissue, preserving the EF and the left ventricular end-diastolic diameter, valve-sparing surgeries should be preferred for appropriate patients.